How the Perception of Public Official on Organizational Culture Influences Procedural Justice in Environmental Policy Processes - Yuan, Meng (Frontiers in Psychology, 2021)
How does the organizational culture of local governments influence the type and extent of procedural justice in environmental policy processes? Using Culture Theory developed by Mary Douglas, Aaron Wildavsky, and others, this research seeks to bring a new conception and new measures of organizational culture to the study of policy making by local governments. To contribute to developing the conceptualization and measurement of procedural justice in the environmental policy processes of those governments, IRT Graded Response Model is used to show variations of difficulties and frequencies of adopting distinctive public participation strategies for improving procedural justice across local governments. I use original survey data from Illinois municipalities and find that cultural variables explain two dimensions of procedural justice-equal and authentic public participation while other variables can, at best, explain only the equal public participation. Moreover, as hypothesized, egalitarianism increases both equal and authentic public participation, individualism increases equal public participation, and fatalism decreases them.